Adenosine A2A Receptor Signaling in the Immunopathogenesis of Experimental Autoimmune Encephalomyelitis - Rajasundaram, Skanda (Frontiers in Immunology, 2018)
Our increasing appreciation of adenosine as an endogenous signalling molecule that terminates inflammation has generated excitement regarding the potential to target adenosine receptors in the treatment of Multiple Sclerosis, a disease of chronic neuroinflammation. Of the four G protein-coupled adenosine receptors (ARs), A2ARs are the principal mediator of adenosine’s anti-inflammatory effects and accordingly, there is a growing body of evidence surrounding the role of A2ARs in Experimental Autoimmune Encephalomyelitis, the dominant animal model of MS. Such evidence points to a complex, often paradoxical role for A2ARs in the immunopathogenesis of EAE, where they have the ability to both exacerbate and alleviate disease severity. This review seeks to interpret these paradoxical findings and evaluate the therapeutic promise of A2ARs. In essence, the complexities of A2AR signalling arise from its capacity to downregulate the inflammatory potential of TH lymphocytes whilst simultaneously facilitating the recruitment of these cells into the CNS and additionally, from the capacity of A2AR signalling in myeloid cells – infiltrating macrophages and CNS-resident microglia - to promote both tissue injury and repair in chronic neuroinflammation. Consequently, the therapeutic potential of targeting A2ARs is greatly undermined by the risk of collateral tissue damage in the periphery and/or CNS.